A critical study of the legal framework for shari'ah governance in Islamic banking in Nigeria and Malaysia - Bello, Shafi'i Abdul Azeez (Ahmad Ibrahim Kulliyyah of Laws , International Islamic University Malaysia, 2016)
For the first time in the history of Nigerian Banking Laws, Banks and Other Financial Institutions Act (BOFIA No. 25), 1991 permitted the establishment of Profit and Loss Sharing (PLS) banking which is the stamp of authenticity of Islamic Banking system. However, years after the promulgation of the Act, the establishment of Islamic banking system has been made unachievable by the narrow constituted by the same law and other banking related laws, governmental policies and the attitude of the Muslim populace amongst others. Therefore, this research studies the legal framework of SharÊÑah governance in Islamic banking in Nigeria and Malaysia. It was conducted vide qualitative research methodology. It involves both doctrinal and non-doctrinal research. It was revealed that although PLS banking system is approved by the main Nigerian banking law, yet, its provisions are restrictive and lacking in comprehensiveness requisite of the system's smooth operations. Interest based economic system and fiscal policies of the government, pervading corruption, porous legislative process, the prevailing religious bigotry and lack of legal framework for SharÊÑah governance were identified as threats not only to the establishment but also to the smooth operations of Islamic banking system in Nigeria. The significance of this research lies in the identification and prospects of the foregoing problems and the solutions proffered to avert or limit their negative consequences. The likelihoods that could be taken advantage of, to enhance the possibility of the establishment and operations of SharÊÑah governance framework for Islamic banking system were as much highlighted. However, this research discusses the regulatory framework of the SharÊÑah governance system of the two respective jurisdictions; Malaysia and Bahrain as they provide different distinctive models. Uniquely, the models of SharÊÑah governance of both respective jurisdictions can serve as models for the effective legal framework for SharÊÑah governance of Islamic banking in Nigeria. Unambiguously, it is a sine qua non for the significant differences of SharÊÑah governance system. As from the regulatory overview, Malaysia represents mixed-model legal jurisdiction which is regulatory-based approach and Bahrain represents mixed-model legal environment which is minimalists approach. This research suggests that both regulatory frameworks of SharÊÑah governance system need further enhancement and improvement in order to reinforce the development and growing of Islamic finance industry. This brings into focus the measures and efforts that need to be taken to strengthen the IFIs in Nigeria through enhancing the SharÊÑah governance framework. Also, a sound judicial system and Islamic dispute resolution mechanism in Nigeria are key factors that would help in attracting foreign investors, particularly from the oil rich countries, to invest in the nascent IB industry in Nigeria. Therefore, the models of dispute resolution context that can be easily domesticated into existing mechanisms of dispute resolution are the models of dispute resolution of countries like Malaysia and Pakistan as they have similar colonial histories as Nigeria, and in fact, the element of legal pluralism is another similar trail that these countries share. So, borrowing a leaf from such best practices will help in solving matters in the IB industry in Nigeria. The research concluded that a failure to provide efficient Shareah governance framework either through law or legislation on the part of regulators and the banking sector would inevitably lead to serious disruptions in Islamic finance industry in Nigeria.